Chondroblastoma of the distal femoral metaphysis: A case report with emphasis on imaging findings and differential diagnosis. Issue 17 (April 2018) - Wang, Fang; Li, Jizhen; Yu, Dexin; Wang, Qing
Abstract : Abstract: Chondroblastoma is a rare benign tumor, consisting of tissue resembling foetal cartilage, and arising in the epiphyses, or apophyses of long tubular bone. However, chondroblastoma of the cortex of the long bone metaphysis is extremely rare. A 15-year-old girl presented a 10-month history of intermittent knee pain and without mobility limitation. X ray, computed tomography (CT), and magnetic resonance imaging (MRI) showed a slightly expansile lytic lesion involving the metaphyseal cortex of the left distal femur. During histological examination, typical features of chondroblastoma were observed. Chondroblastoma was definitely and histologically diagnosed. Surgical procedures included intralesional tumor curettage and allograft bone implantation. The patient was discharged without any complications 1 week after surgery and there was no recurrence during a 10-month follow-up. This report describes a case of chondroblastoma in the metaphyseal cortex of the distal femur and serves as a reminder of the atypical anatomic location of chondroblastoma. Patients in an appropriate age group with typical imaging features may be diagnosed with chondroblastoma despite its rare location.